2019
DOI: 10.3892/or.2019.6957
|View full text |Cite
|
Sign up to set email alerts
|

CX3CL1 promotes lung cancer cell migration and invasion via the Src/focal adhesion kinase signaling pathway

Abstract: The present study investigated the role of C-X3-C motif chemokine ligand 1 (CX3CL1) in lung cancer cell migration and invasion and its potential mechanism. The expression levels of C-X3-C motif chemokine receptor 1 (CX3CR1) in six human lung cancer cell lines and one human bronchial epithelial cell line were assessed using reverse transcription-quantitative polymerase chain reaction and western blotting. Cell proliferation was assessed using the Cell Counting Kit-8 assay. Cell migration and invasion were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…42 Other data provided evidence that both uPAR and suPAR are capable of downregulating the tumor suppressor PTEN in endothelial cells to support angiogenesis. 43 In our study, we found a positive correlation between initial suPAR levels and cytokines (CXCL5, CX3CL1 and IL-8) with a known promalignant function in BTC and other malignancies, [26][27][28][29] suggesting that circulating suPAR might also reflect a more aggressive individual tumor biology. However, functional data in the context of BTC are still limited and further molecular studies are warranted to elucidate the underlying pathophysiology of increased uPAR/suPAR expression and impaired survival in patients with BTC.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…42 Other data provided evidence that both uPAR and suPAR are capable of downregulating the tumor suppressor PTEN in endothelial cells to support angiogenesis. 43 In our study, we found a positive correlation between initial suPAR levels and cytokines (CXCL5, CX3CL1 and IL-8) with a known promalignant function in BTC and other malignancies, [26][27][28][29] suggesting that circulating suPAR might also reflect a more aggressive individual tumor biology. However, functional data in the context of BTC are still limited and further molecular studies are warranted to elucidate the underlying pathophysiology of increased uPAR/suPAR expression and impaired survival in patients with BTC.…”
Section: Discussionmentioning
confidence: 65%
“…Subsequently, we included parameters with a p value <0.250 in univariate analyses into multivariate Cox-regression analysis which revealed initial suPAR concentrations to be an independent prognostic factor in the context of BTC resection (Table 2). Finally, we measured serum levels of CXCL5, CX3CL1 and IL-8, representing cytokines with a known pro-malignant function in BTC cancer and other malignancies [26][27][28][29] to gain further information on the association between elevated suPAR levels and impaired outcomes. Importantly, we observed a positive correlation between all 3 cytokines and circulating suPAR levels, suggesting that suPAR might also reflect a pro-malignant tumor biology in patients with BTC (Table S3).…”
Section: Validation Of the Prognostic Relevance Of Circulating Suparmentioning
confidence: 99%
“…Chemokines are directly implicated in a series of cellular functions, including cell proliferation, migration, and invasion 26 . Liu et al demonstrate that CX3CL1 promotes lung cancer cell migration and invasion through the Src/ FAK signaling pathway 27 . In intrahepatic cholangiocarcinoma, higher expression of CXCL12 is associated with metastasis and poor prognosis 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Src interacts with other transmembrane receptors, such as integrins/Focal adhesion kinase (FAK) and G-protein-coupled receptors (GPCRs), to upregulate their downstream signaling [ 28 , 29 , 30 ]. Regarding human NSCLC, previous studies have shown that the overexpression of Src is associated with poor prognosis and the promotion of migration, invasion, metastasis, and drug resistance [ 31 , 32 , 33 , 34 ]. EGFR kinase domain mutations, such as L858R and exon 19 deletion, are the most frequent oncogenic-driven mutations in human NSCLC (5–15% in Caucasians and 40–55% in East Asians), and EGFR-tyrosine kinase inhibitors (TKIs) have been developed as an effective therapy for advanced EGFR-mutated NSCLC [ 35 , 36 , 37 ].…”
Section: Src In Nsclcmentioning
confidence: 99%
“…EGFR kinase domain mutations, such as L858R and exon 19 deletion, are the most frequent oncogenic-driven mutations in human NSCLC (5–15% in Caucasians and 40–55% in East Asians), and EGFR-tyrosine kinase inhibitors (TKIs) have been developed as an effective therapy for advanced EGFR-mutated NSCLC [ 35 , 36 , 37 ]. EGFR kinase domain mutations activate downstream signaling pathways, including the mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK), phosphatidylinositol 3-kinase (PI3K)/Akt/mTOR, and interleukin 6 (IL-6)/Janus kinase (JAK)/signal transducer, and the activator of transcription 3 (STAT3) signaling pathways [ 34 ]. Several previous studies have provided evidence that Src activates the three downstream signaling pathways (MAPK/ERK, PI3K/Akt/mTOR, and IL-6/JAK/STAT3), thus promoting resistance to EGFR-TKIs in NSCLC [ 38 , 39 ].…”
Section: Src In Nsclcmentioning
confidence: 99%